PENGARUH KURANG ENERGI KRONIS DAN ANEMIA IBU HAMIL TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH - Setyaningrum, Dyah Ayu; Estiwidani, Dwiana; Sumarah, Sumarah (Jurnal Kesehatan Ibu dan Anak, 2013)
The neonatal mortality rate in the world is about 29 % because Low Birth weight (LBW). In Indonesia, the highest mortality cause is LBW. LBW rate in Gunungkidul increase from 2,76%to 3,92%. LBW rate in Hospital Wonosari is 15,9% from 1346 birth rate. One of predisposition factors of LBW is pregnant mother with KEK and anemia. The rate of KEK have Increase from 15,91 % to 15,44 %, and anemia rate have increase from 13,97o/o to 15,22 %. Knowing effect of KEK and anemia of pregnant mother to LBW at Hospital Wonosari 2012. Research sing observational analytic with case control design. Sample technic using randomizes from delivery mother medical record at RSUD Wonosari. Sample consist of case and control group 1:1 65 LBW for case and 65 normal birth weight for control. This research using correlation test Chi Square, Odds Ratio and Logistic Regression. LBW from pregnant mother with KEK 61,54%, non KEK 38,46%, normal birth weigh from pregnant mother with KEK 23,07%, non KEK 76,93%. LBW from pregnant mother with anemia 63,07%, non-anemia 36,93 %, normal birth weigh from pregnant mother with anemia 23,07 %, non-anemia 76,93 %. Pregnant mother with KEK is have risk 5,33 higher for delivering LBW. Pregnant mother with anemia is have risk 5,67 higher for delivering LBW. There is effect from KEK and anemia of pregnant mother to LBW. Anemia have more effect causing LBW. There is effect from KEK and anemia of pregnant mother to LBW. Anemia have more effect causing LBW.